COVID-19 vaccine coverage and factors associated with vaccine uptake among 23 247 adults with a recent history of homelessness in Ontario, Canada: a population-based cohort study - Salimah Z Shariff, PhD; Lucie Richard, MA; Stephen W Hwang, ProfMD; Jeffrey C Kwong, ProfMD; Cheryl Forchuk, ProfPhD; Naheed Dosani, MD; Richard Booth, PhD (Elsevier, 2022)
Summary: Background: People experiencing homelessness face a high risk of SARS-CoV-2 infection and transmission, as well as health complications and death due to COVID-19. Despite being prioritised for receiving the COVID-19 vaccine in many regions, little data are available on vaccine uptake in this vulnerable population. Using population-based health-care administrative data from Ontario, Canada-a region with a universal, publicly funded health system-we aimed to describe COVID-19 vaccine coverage (ie, the estimated percentage of people who have received a vaccine) and determinants of vaccine receipt among individuals with a recent history of homelessness. Methods: We conducted a retrospective, population-based cohort study of adults (aged ≥18 years) with a recent experience of homelessness, inadequate housing, or shelter use as recorded in routinely collected health-care databases between June 14, 2020, and June 14, 2021 (a period within 6 months of Dec 14, 2020, when COVID-19 vaccine administration was initiated in Ontario). Participants were followed up from Dec 14, 2020, to Sept 30, 2021, for the receipt of one or two doses of a COVID-19 vaccine using the province's real-time centralised vaccine information system. We described COVID-19 vaccine coverage overall and within predefined subgroups. Using modified Poisson regression, we further identified sociodemographic factors, health-care usage, and clinical factors associated with receipt of at least one dose of a COVID-19 vaccine. Findings: 23 247 individuals with a recent history of homelessness were included in this study. Participants were predominantly male (14 752 [63·5%] of 23 247); nearly half were younger than 40 years (11 521 [49·6%]) and lived in large metropolitan regions (12 123 [52·2%]); and the majority (18 226 [78·4%]) visited a general practitioner for an in-person consultation during the observation period. By Sept 30, 2021, 14 271 (61·4%; 95% CI 60·8-62·0) individuals with a recent history of homelessness had received at least one dose of a COVID-19 vaccine and 11 082 (47·7%; 47·0-48·3) had received two doses; in comparison, over the same period, 86·6% of adults in the total Ontario population had received a first dose and 81·6% had received a second dose. In multivariable analysis, factors positively associated with COVID-19 uptake were one or more outpatient visits to a general practitioner (adjusted risk ratio [aRR] 1·37 [95% CI 1·31-1·42]), older age (50-59 years vs 18-29 years: 1·18 [1·14-1·22], ≥60 years vs 18-29 years: 1·27 [1·22-1·31]), receipt of an influenza vaccine in either of the two previous influenza seasons (1·25 [1·23-1·28]), being identified as homeless via a visit to a community health centre versus exclusively a hospital-based encounter (1·13 [1·10-1·15]), receipt of one or more SARS-CoV-2 tests between March 1, 2020, and Sept 30, 2021 (1·23 [1·20-1·26]), and the presence of chronic health conditions (one condition: 1·05 [1·03-1·08]; two or more conditions: 1·11 [1·08-1·14]). By contrast, living in a smaller metropolitan region (aRR 0·92 [95% CI 0·90-0·94]) or rural location (0·93 [0·90-0·97]) versus large metropolitan regions were associated with lower uptake. Interpretation: In Ontario, COVID-19 vaccine coverage among adults with a recent history of homelessness has lagged and, as of Sept 30, 2021, was 25 percentage points lower than that of the general adult population in Ontario for a first dose and 34 percentage points lower for a second dose. With high usage of outpatient health services among individuals with a recent history of homelessness, better utilisation of outpatient primary care structures might offer an opportunity to increase vaccine coverage in this population. Our findings underscore the importance of leveraging existing health and service organisations that are accessed and trusted by people who experience homelessness for targeted vaccine delivery. Funding: The Public Health Agency of Canada. Translation: For the French translation of the abstract see Supplementary Materials section.